Depth-resolved photochemical production of hydrogen peroxide in the global ocean using remotely sensed ocean color - Zhu, Yuting; Powers, Leanne C.; Kieber, David J.; Miller, William L. (Frontiers in Remote Sensing, 2022)
Hydrogen peroxide (H2O2) is an important reactive oxygen species (ROS) in natural waters, affecting water quality via participation in metal redox reactions and causing oxidative stress for marine ecosystems. While attempts have been made to better understand H2O2 dynamics in the global ocean, the relative importance of various H2O2 sources and losses remains uncertain. Our model improves previous estimates of photochemical H2O2 production rates by using remotely sensed ocean color to characterize the ultraviolet (UV) radiation field in surface water along with quantitative chemical data for the photochemical efficiency of H2O2 formation. Wavelength- and temperature-dependent efficiency (i.e., apparent quantum yield, AQY) spectra previously reported for a variety of seawater sources, including coastal and oligotrophic stations in Antarctica, the Pacific Ocean at Station ALOHA, the Gulf of Mexico, and several sites along the eastern coast of the United States were compiled to obtain a “marine-average” AQY spectrum. To evaluate our predictions of H2O2 photoproduction in surface waters using this single AQY spectrum, we compared modeled rates to new measured rates from Gulf Stream, coastal, and nearshore river-outflow stations in the South Atlantic Bight, GA, United States; obtaining comparative differences of 33% or less. In our global model, the “marine-average” AQY spectrum was used with modeled solar irradiance, together with satellite-derived surface seawater temperature and UV optical properties, including diffuse attenuation coefficients and dissolved organic matter absorption coefficients estimated with remote sensing-based algorithms. The final product of the model, a monthly climatology of depth-resolved H2O2 photoproduction rates in the surface mixed layer, is reported for the first time and provides an integrated global estimate of ∼21.1 Tmol yr−1 for photochemical H2O2 production. This work has important implications for photo-redox reactions in seawater and improves our understanding of the role of solar irradiation on ROS cycling and the overall oxidation state in the oceans.